Anomalous origin of the right pulmonary artery from the ascending aorta in 6-week-old infant - Werner, Bożena; Tomik, Agnieszka; Gołąbek-Dylewska, Małgorzata; Godlewski, Krzysztof; Karolczak, Maciej A. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The authors present 6-week-old-male baby with the anomalous origin of the right pulmonary artery from the ascending aorta resulting in heart failure. The anomaly was diagnosed with echocardiography and confirmed by angiography. He was operated on, the direct end -to-side anastomosis of the right pulmonary artery to the main pulmonary trunk was performed with good results.